Analysis of individual and social effects of creative events. Issue 2 (3rd July 2017) - Seyfi, Murat; Güven, Deniz
Abstract : Events have been an important part of the life throughout the history of humanity. Throughout the history, people not only entertained themselves with events but also they handed down social and cultural knowledge from generation to generation. Now, traditional events have to change and develop themselves in the human life which changed through modernity. Therefore, event managers have focused on engaging in activities which could influence satisfaction and loyalty of the audience by organising creative events in the recent years. It is now an obligation to study both social and individual effects of these events. The aim of this study is to analyse individual and social effects of a creative event. Within this framework, social media statements about the event titled "dialogue in the dark", which was organised in Istanbul, shared by individuals who participated in this event were analysed via the method of content analysis. Acquired qualitative data was discussed by being categorised.